The effect of addition nano particle ZrO2 on some properties of autoclave processed heat cure acrylic denture base material - Hameed, Hussein K; Abdul Rahman, Hanan (Journal of Baghdad College of Dentistry, 2015)
Background: Polymethyl methacrylate (PMMA) is used in denture fabrication and considered as the most reliable material for the construction of removable prosthodontic appliances. The material is far from ideal in fulfilling the mechanical requirements and the effect of autoclave processing has not been fully determined. The purpose of this study was to evaluate the effect of addition of salinized (ZrO2) Nano fillers in percentages 3%, 5% and 7% by weight on some properties of heat cured acrylic processed the by autoclave and compare it with 0% (control) group . Materials and methods: The silanized(ZrO2) Nano-particles was added to PMMA powder by weight in three different percentages 3%, 5% and 7%, mixed by probe ultra-sonication machine.Two hundred specimens were constructed and processed by autoclave and divided into 5 groups according to the test (each group consist of 40 specimens ) and each group was subdivided into 4 sub-groups according to the percentage of added (ZrO2) nano-particles( with 10 specimens for each subgroups) . The tests conducted were transverse strength, hardness (shore D), Impact strength test, surface morphology and apparent porosity. AFM can provide 3D image of the specimen the homogeneity of nanostructure film, roughness of surface and crystallite size. Scanning electron microscope SEM of control and salinized Nano ZrO2 reveal the Nano fillers distribution and it is shaped. Results: Highly significant increase in impact strength recorded when acrylic (vertex) mixed with 3%, 5% ZrO2 nano filler, while a non-significant reduction was observed with 7% ZrO2 addition in comparison to control. Non-significant improvement in transverse strength when 3% ZrO2 was added, 5% nano addition ZrO2 improved transverse strength significantly while 7% nano addition showed anon significant reduce when these groups compared to the control group .Anon significant reduction in the deformity was seen within 3% nano addition ZrO2 also 5% nano ZrO2 addition reduce the deformity significantly and significant increase was recorded when 7% nano addition ZrO2 was add and when these groups are compared to the control group. A significant increase in surface hardness was observed with the addition of (ZrO2) nano-particles to (PMMA) at the percentage of 3%, highly significant increase at 5% and 7% with addition of modified nano-ZrO2. A non-significant decrease in apparent porosity at 3% and highly significant decrease in apparent porosity at 5% and 7% with addition of modified nano-ZrO2 were observed. SEM results showed a good distribution of the modified nano-ZrO2 fillers at 3%, 5% and showed aggregation at 7% in the polymer matrix. Conclusion: The addition of modified nano-ZrO2 particles to acrylic resin cured by autoclave improved impact and transverse strength of denture base nano composite containing 5% of nano-ZrO2. And this strength decreases with further increase of nano-ZrO2 filler content. Also addition of modified nano-ZrO2 slightly increaseshardness, thesurface roughness and the apparent porosity also decrease by addition of nano ZrO2 percentage increase. Key words: Salinized (ZrO2) nano fillers, PMMA.